Accelerometer derived load according to playing position in competitive youth soccer - Barron, D. J; Atkins, S.; Edmundson, C.; Fewtrell, D. (International Journal of Performance Analysis in Sport, 2014)
The integration of accelerometers and Global Positioning Systems (GPS) provides the opportunity to objectively measure a players work output Although these systems have been widely adopted at the elite level, a positional profile of the external demands of soccer is currently missing from the literature. This study aimed to investigate the acceleration, deceleration and triaxial player load during competitive youth football. Eight 11v11 games were monitored during the competitive phase of the 2012-2013 season, using Catapult Minimax 5Hz GPS and 100Hz accelerometers. Analysis showed that wide midfielders completed significantly more maximal acceleration and deceleration actions. There were no reductions between playing halves in maximal acceleration or deceleration actions, across all playing positions. Central midfielders had a significantly higher total load, and a higher Y axis load compared to central defenders.